Scalp acupuncture regulates functional connectivity of cerebral hemispheres in patients with hemiplegia after stroke - Lin, Dan; Gao, Jinyang; Lu, Mengxin; Han, Xiao; Tan, Zhongjian; Zou, Yihuai; Cui, Fangyuan (Frontiers in Neurology, 2023)
Background Stroke is a common cause of acquired disability on a global scale. Patients with motor dysfunction after a stroke have a reduced quality of life and suffer from an economic burden. Scalp acupuncture has been proven to be an effective treatment for motor recovery after a stroke. However, the neural mechanism of scalp acupuncture for motor function recovery remains to be researched. This study aimed to investigate functional connectivity (FC) changes in region of interest (ROI) and other brain regions to interpret the neural mechanism of scalp acupuncture. Methods Twenty-one patients were included and randomly divided into patient control (PCs) and scalp acupuncture (SAs) groups with left hemiplegia due to ischemic stroke, and we also selected 20 matched healthy controls (HCs). The PCs were treated with conventional Western medicine, while the SAs were treated with scalp acupuncture (acupuncture at the right anterior oblique line of vertex temporal). All subjects received whole-brain resting-state functional magnetic resonance imaging (rs-fMRI) scan before treatment, and the patients received a second scan after 14 days of treatment. We use the National Institutes of Health Stroke Scale (NIHSS) scores and the analyses of resting-state functional connectivity (RSFC) as the observational indicators. Results The contralateral and ipsilateral cortex of hemiplegic patients with cerebral infarction were associated with an abnormal increase and decrease in basal internode function. An abnormal increase in functional connectivity mainly exists in the ipsilateral hemisphere between the cortex and basal ganglia and reduces the abnormal functional connectivity in the cortex and contralateral basal ganglia. Increased RSFC was observed in the bilateral BA6 area and bilateral basal ganglia and the connectivity between bilateral basal ganglia nuclei improved. However, the RSFC of the conventional treatment group only improved in the unilateral basal ganglia and contralateral BA6 area. The RSFC in the left middle frontal gyrus, superior temporal gyrus, precuneus, and other healthy brain regions were enhanced in SAs after treatment. Conclusion The changes in functional connectivity between the cerebral cortex and basal ganglia in patients with cerebral infarction showed a weakening of the bilateral hemispheres and the enhancement of the connections between the hemispheres. Scalp acupuncture has the function of bidirectional regulation, which makes the unbalanced abnormal brain function state restore balance.